The performance of nationalism : India, Pakistan, and the memory of partition - Menon, Jisha (New Delhi : Cambridge University Press, 2013)
"The Performance of Nationalism: India, Pakistan and the Memory of Partition."--
Keywords: Nationalism in literature; Partition, Territorial, in literature